First Isolation of Yarrowia lipolytica in a Granulomatous Pneumonia of a Spectacled Caiman, Caiman crocodilus Linnaeus, 1758 - Manuela Iurescia; Andrea Santini; Marco Montagnani; Elena Lavinia Diaconu; Fiorentino Stravino; Devid Agnelli; Emanuela Vergari; Gianluca Fichi; Claudia Eleni (Pathogens, 2022)
Contrary to humans, candidiasis is a rare infection in animals. However, in reptiles, candidiasis can cause gastrointestinal, cutaneous, or rarely systemic infections in stressed animals. The infections due to Yarrowia lipolytica have been increasingly described in human medicine, and hundreds of cases are reported, comprised of granulomatous lung lesions. Herein, granulomatous pneumonia of a spectacled caiman, Caiman crocodilus, was described, and the presence of Y. lipolytica in the lesion was confirmed through histopathology, microbiologic cultures, and molecular methods. The cause of death of the spectacled caiman was ascribed to bacterial shock septicemia consequentially to a traumatic lesion. However, in the right lung, several nodules containing white exudate were evidenced. At mycological and molecular analyses, Y. lipolytica was evidenced, and the histological finding confirmed the presence of a Candida infection in the lung granulomatous lesions. The comparison of ITS sequences with 11 Yarrowia spp. isolates, recently described in green sea turtles, and with a human strain was conducted, and the whole genome of a strain isolated in the spectacled caiman was sequenced. Even though Y. lipolytica is considered a non-pathogenic yeast and has been rarely described in animals, it seems to cause granulomatous lesions in reptiles as in humans.